Dental age in patients with neurofibromatosis 1 - Jääsaari P; Visnapuu V; Nyström M; Peltonen S; Peltonen J; Happonen RP (WILEY-BLACKWELL, 2022)
Neurofibromatosis type 1 (NF1) is a common, hereditary, neurocutaneous skeletal condition with a variety of osseous manifestations. Although NF1 also affects craniofacial structures, the literature has only limited information related to the effect of NF1 on dental development. In this study the dental age of 34 Finnish NF1 patients, 817 yr of age, was estimated using the Demirjian & Goldstein method. The dental age of children with NF1 was similar to that of a Finnish control population. The findings suggest that NF1 does not affect the timing of tooth development.